2013
DOI: 10.1017/s0022109013000148
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Marriage to Family Firms

Abstract: This paper presents the first empirical evidence showing that the marriage of a member of the controlling family adds value to public corporations. The results, based on a uniquely comprehensive data set from Thailand, show that the family firm’s stock price increases when the partner is from either a prominent business or a political family. Abnormal returns tend to be higher for firms whose operation depends on extensive networks. In contrast, marriages to ordinary citizens are not associated with any abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…Prior research found that in-laws can play an important role. In public firms, investors favor marriages between well-connected families (Bunkanwanicha et al, 2013). Santiago (2011) found that cohesive and professionally run families better integrate in-laws.…”
Section: 432mentioning
confidence: 99%
“…Prior research found that in-laws can play an important role. In public firms, investors favor marriages between well-connected families (Bunkanwanicha et al, 2013). Santiago (2011) found that cohesive and professionally run families better integrate in-laws.…”
Section: 432mentioning
confidence: 99%
“…However, the glue that binds firms into a group is not limited to formal ownership. The firms can be connected through informal relationships of their key personnel, such as through marriages (Bunkanwanicha et al, 2009), blood ties, school ties, job relationships (Khanna and Thomas, 2009), and so on. The group-like hybrid organizational form (Williamson, 1985) challenges our traditional assumption that firm decision rights are completely decentralized to firm managers, managers compete and collaborate in an arm's length manner, and conflicts are resolved in the court.…”
Section: Network Organizationsmentioning
confidence: 99%
“…One is the factors of network development, and the other is the economic benefits that firms can derive from their networks. The first question has been studied mainly on the political connections [6], [7], which include from marriage [8] to classmate [9]. However, these factors are intrinsically related to the economic benefit through those networks, which refers to the second question.…”
Section: Network In Corporate Financementioning
confidence: 99%